Efektivitas Jenis Bahan Masker Kain Berdasarkan Kemampuan Penyaringan Mikroba: Effectiveness of Fabric Mask Material Types Based on Microbial Filtration Capabilities - Nilam Sari; Mukti Priastomo; Niken Indriyanti (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
A cloth mask is a mask that can be used repeatedly and is made of thicker fabric material. Cloth masks circulating in the community have not guaranteed quality. This study aims to find out the effectiveness of fabric mask materials based on microbial filtration capabilities as well as find out the optimal characteristics of the initial use of cloth mask materials and after washing 50 times. This study was conducted experimentally where the effectiveness of fabric mask material by spraying bacterial suspension, and testing the characteristics of fabric mask materials by conducting fiber observation, light intensity test, steam filtration test, water absorption test and water capillary on the fabric. The results of research on the effectiveness of fabric mask materials showed Asymp.Sig >0.05 so that there are significant differences from all types of fabric mask materials. Based on the results of characteristic testing, the fiber material of the initial cloth mask looks better than after 50 washes. Test the light intensity of the outer layer, inner layer, and filter layers p, f and s after washing there is an increase compared to the initial use. Steam filtration tests of outer layers, inner layers and filter layers p, f and s when the initial user takes time for steam to penetrate the fabric compared to 50 washes. The absorption test of the outer layer during initial use does not occur absorption above 60 seconds and after 50 washes begins absorption. The inner layer and filter layer at the initial use do not absorb above 60 seconds and after 50 washes there is absorption under 60 seconds. The p filter layer does not absorb during initial use and after 50 washes. Filter layer f during initial use and after 50 washes there is absorption under 60 seconds. Capillary test results for 60 seconds the outer layer and the p filter layer during initial use do not absorb while 50 times the washing occurs absorption. The inner layer, filter layer f and s increase after 50 washes. The conclusion of the study was that the effectiveness of the mask material was good enough for the inner and outer layers, the p filter layer was more effective than the f and s filter layers. The characteristic test results at initial use were very good, but after 50 washes there was a decrease.